HUBUNGAN INDEKS MASSA TUBUH DENGAN KADAR HBA1C PADA PENDERITA DIABETES MELITUS TIPE-2 - Salsabila Hurin; Donna Adriani (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2023)
BACKGROUND Diabetes mellitus (DM) is a state of increased sugar levels in the blood vessels. DM can interfere with organ function and cause death. One of the criteria for diagnosing DM based on ADA is HbA1c. In 2019, 463 million people with DM aged 20 to 79 years worldwide. DM sufferers are estimated to increase every year due to risk factors: race, age, gender, lack of physical activity, unhealthy and unbalanced diet, overweight or obesity. Overweight or obesity is detected by calculating the Body Mass Index. The purpose of this study was to determine the relationship between body mass index and HbA1c levels in patients with type-2 diabetes mellitus. METHODS Observational analytic study with cross-sectional design. The total sample is 90 respondents obtained from medical record data at RSUD dr. Soekardjo Tasikmalaya City in type-2 DM patients. Data analysis was performed using Fisher's exact test on the SPSS version 25 program. RESULTS Characteristics of respondents who are >45 years old (82.2%) and female (71.1%). There was no significant relationship between age and HbA1c (p-value = 0.633). There was no significant relationship between BMI and HbA1c (p-value = 0.011). CONCLUSIONS In this study, there was no significant relationship between body mass index and HbA1c levels in patients with type-2 diabetes mellitus. BMI should be considered when using the HbA1c assay to diagnose and manage type-2 diabetes.